2021
DOI: 10.1038/s41598-021-97800-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin ameliorating sterile inflammation induced by low-dose radiation exposure

Abstract: Glycyrrhizin (GL) is a direct inhibitor of HMGB1 which acts as an alarmin when excreted into the extracellular space. High-dose radiation in radiotherapy induces collateral damage to the normal tissue, which can be mitigated by GL inhibiting HMGB1. The purpose of this study was to assess changes in HMGB1 and pro-inflammatory cytokines and to evaluate the protective effect of GL after low-dose radiation exposure. BALB/c mice were irradiated with 0.1 Gy (n = 10) and 1 Gy (n = 10) with GL being administered to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In acute lung injury and hepatic ischemia-reperfusion injury models, administration of anti-HMGB1 antibody reduces lung neutrophil influx and pulmonary edema and mitigates liver damage ( 67 , 68 ). Exposure to ionizing radiation increases in both cellular mRNA expression and serum protein levels of HMGB1 in a dose-dependent manner in experimental mice model ( 69 ). Glycyrrhizin, one of the inhibitors of HMGB1, reduced the release of serum inflammatory cytokines in abdominal irradiated mice (6.5 Gy) through the downregulation of the HMGB1/TLR4 signaling pathway and significantly attenuated intestinal injury ( 50 ).…”
Section: Damp Release After Radiation Injurymentioning
confidence: 99%
“…In acute lung injury and hepatic ischemia-reperfusion injury models, administration of anti-HMGB1 antibody reduces lung neutrophil influx and pulmonary edema and mitigates liver damage ( 67 , 68 ). Exposure to ionizing radiation increases in both cellular mRNA expression and serum protein levels of HMGB1 in a dose-dependent manner in experimental mice model ( 69 ). Glycyrrhizin, one of the inhibitors of HMGB1, reduced the release of serum inflammatory cytokines in abdominal irradiated mice (6.5 Gy) through the downregulation of the HMGB1/TLR4 signaling pathway and significantly attenuated intestinal injury ( 50 ).…”
Section: Damp Release After Radiation Injurymentioning
confidence: 99%
“…The high mobility group box-1/toll-like receptor4/nuclear factor-kappa B signaling pathway HMGB1, as a protein of the 215 amino acids, is located in a stable environment of the nucleus. In healthy cells, HMGB1 plays a non-histone role in the nucleus that is key to maintain the nucleosome stability and DNA transcription (Kim et al, 2021). HMGB1 can be secreted via two ways: One is actively secreted by the immune system as a warning signal during cell stress; the other is aggressively secreted by the necrotic cells (Manivannan et al, 2020).…”
Section: Astrocytic Activationmentioning
confidence: 99%
“…37 Kim et al have reported that pretreatment with glycyrrhizic acid can effectively alleviate radiation damage and oxidative stress and improve cell survival rates in mice exposed to low-dose radiation. 38 Therefore, licorice and GL can reduce radiation damage by regulating immunity, relieving inflammation, and eliminating oxidants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chen et al demonstrated that glycyrrhizic acid can effectively alleviate the multiorgan inflammatory response caused by radiation injury of mice skin, and achieve the effect of radiation therapy and protection . Kim et al have reported that pretreatment with glycyrrhizic acid can effectively alleviate radiation damage and oxidative stress and improve cell survival rates in mice exposed to low-dose radiation . Therefore, licorice and GL can reduce radiation damage by regulating immunity, relieving inflammation, and eliminating oxidants.…”
Section: Introductionmentioning
confidence: 99%